Anthropometric Measures in Adolescents With Inflammatory Bowel Disease: A Population-Based Study. Issue 6 (24th October 2018) - Ghersin, Itai; Khateeb, Neron; Katz, Lior H; Daher, Saleh; Shamir, Raanan; Assa, Amit
Abstract: Background: Growth impairment is common in pediatric inflammatory bowel disease (IBD) patients. Nevertheless, a controversy exists regarding disease impact on anthropometric measures in the long term. Thus, we aimed to investigate the impact of IBD on anthropometric measures, including weight, height, and body mass index (BMI), during late adolescence in a cross-sectional, population-based study. Methods: A total of 1, 144, 213 Jewish Israeli adolescents who underwent a general health examination from 2002 to 2016 at a median age (interquartile range) of 17.1 (16.9–17.3) years were included. Inflammatory bowel disease cases were stratified into Crohn's disease (CD) and ulcerative colitis (UC). Patients were also subgrouped based on age at IBD diagnosis. Results: Overall, 2372 cases of IBD were identified out of 1, 144, 213 persons examined (0.2%). Crohn's disease accounted for 68% of IBD cases. Males and females with CD (but not with UC) had significantly lower weight and BMI compared with controls. Differences in height at late adolescence were not statistically significant for either disease compared with controls (females: 162 cm vs 161.7 cm vs 161.5 cm; males: 174 cm vs 173.7 cm vs 173.6 cm for controls, UC, and CD, respectively). In a subgroup analysis, patients with CD diagnosed at age <14 years were significantly shorter than controls (males: 172.7 cm vs 174 cm; P = 0.001; females: 160.6 cm vs 162; P = 0.008). This pattern was not noted in UC patients. Conclusions: Adolescents with CD were leaner compared with the general population. No overall difference was noted in height at late adolescence. Younger age at diagnosis was associated with reduced height in CD patients.